Local structure orders and glass forming ability of Ni-Nb liquids. (July 2018) - Wen, T.Q.; Zhang, Y.; Wang, C.Z.; Wang, N.; Ho, K.M.; Kramer, M.J.
Abstract: Ab initio molecular dynamics simulations were performed to study the atomistic structures of Ni48 Nb52, Ni59.5 Nb40.5 and Ni75 Nb25 liquids near their melting temperatures. It is found that the total coordination number only changes slightly across the compositions. However, there is significant difference in the chemical ordering. The Cluster Alignment method was used to identify the dominant local structure motifs. It is found that distorted and perfect icosahedral clusters are the most popular motifs around Ni atoms, while Z14, Z15, and Z16 Frank-Kasper polyhedra are dominant around Nb atoms. Among the three compositions, the eutectic composition (Ni59.5 Nb40.5 ) has the largest population of these dominant motifs and the highest degree of five-fold local symmetry. Chemical order in the distorted icosahedral motif is studied and the occupation probability of Nb in the distorted region is found to be much different from other sites. The network formed by distorted and perfect icosahedral clusters and that by the interconnection of the perfect icosahedra, Z14, Z15, and Z16 motifs are the strongest at the eutectic composition. The high percentage of perfect and distorted icosahedral clusters and their strong network structures in this system (especially around the eutectic composition) correlate well with the excellent glass forming ability in this system. Highlights: A new distorted icosahedron motif is most popular around Ni in Ni-Nb liquids. The local structure distortion in the new motif is driven by the chemical order of Ni3 Nb phase. Popular motifs around Nb centers in Ni-Nb liquid are Z14, Z15, and Z16 Frank-Kasper polyhedra. The icosahedral-like local structures contribute to the good glass formability around the eutectic point.